The Influence of Talent Management Practice, Training, Job Satisfaction on Employee Performance: The Mediating Role of Employee Engagement - Andi Muhammad Sabilillah Tahir (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to find the factors that influence employee performance through employee engagement. This study used a qualitative literature review method. As a result of this study, several variables strongly support improving employee performance. No respondents were used in this study. Previous articles have been used and analyzed. Related to the research title. The results of this study show that there is a significance between the independent and dependent variables which are proven to be interconnected. The findings of this study are that the employee engagement variable plays a very important role in bridging the employee performance variables, supported by thirteen previous research literature reviews.